2017
DOI: 10.15376/biores.12.2.3890-3904
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cationic CMP and Softwood Long Fibers as Strength-Enhancing Additive to CMP Pulp

Abstract: aCompared to chemical pulp, mechanical and chemi-mechanical pulps (CMP) are limited in regards to the manufacturing of high quality paper. Chemical additives are an effective way to enhance the properties of paper; however, the effectiveness depends on the additive type and dosage. The utilization of cationized natural polymers has been shown to offer a promising solution. In this study, softwood long fiber (SLF) and CMP were cationized by 3-chloro-2-hydroxypropyl-trimethylammoniumchloride (CHPTAC), and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…A considerable improvement in the tensile strength and air permeability of CMP paper was reported when cellulose nanofibers were applied as an additive (Aliniyay Lakani et al 2016). In addition, reports about the cationization of additives on the performance of CMP paper showed that mixing long cationic fibers in CMP paper pulp increased the strength and the retention of fines (Rashidi Jouybari et al 2015). Rahmaninia et al (2015) investigated effects of pH on the performance of chitosanbentonite additives in CMP paper and found that a 1.25% chitosan treatment at a constant level of 0.3% bentonite at an alkaline pH had the best paper strength.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable improvement in the tensile strength and air permeability of CMP paper was reported when cellulose nanofibers were applied as an additive (Aliniyay Lakani et al 2016). In addition, reports about the cationization of additives on the performance of CMP paper showed that mixing long cationic fibers in CMP paper pulp increased the strength and the retention of fines (Rashidi Jouybari et al 2015). Rahmaninia et al (2015) investigated effects of pH on the performance of chitosanbentonite additives in CMP paper and found that a 1.25% chitosan treatment at a constant level of 0.3% bentonite at an alkaline pH had the best paper strength.…”
Section: Introductionmentioning
confidence: 99%